Recommendations of Pope Francis on Rhetoric - Marian Šuráb (Polonia Sacra, 2022)
Pope Francis cares about the quality of homilies. He confirmed this in the exhortation Evangelii gaudium, in which he presented twenty-four points on the homily. Several of them contain recommendations about the manner of preaching. Strong content is not enough for a good homily; the presentation must be appropriate. Ancient and Christian rhetoric as well as modern communication theory all deal with the quality of discourse. The Pope reiterated the importance of the preacher to speak properly, use appropriate language, speak simply and clearly, be mindful of the vocal aspect of their speech, to use appropriate gestures and not to speak for  too long.